PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA HI GADGET STORE - Riki, Riki (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2018)
Hi Gadget Store is an electronics store that provides gadgets which requires an expansion on sales and promotion of its products for customer inside and outside Batam. Hi Gadget Store is still using Banner for its promotion and the recording transaction are still manual so it is likely to make a mistake and a data loss. At the time, the way of purchase at Hi Gadget Store are the customer directly came into the store to see and ordering products that are provided by the store. By developing a web-based sales information system on the Hi Gadget Store, it would help the store and the customer on making transactions and helps the store to promote the store’s products over the internet. The system is using DFD (Data Flow Diagram) for the method development and CMS (Content Management Software) called Opencart for the web-based system. The results of web-based sales information system research could be implemented and be a good use for the store on promoting its product and easily making transactions to the customers.